Bases metodológicas de la investigación educativa y paradigmas - Sáez Alonso, Rafael (Revista Complutense de Educación, 2021)
Since ancient times, there has been a desire to learn about reality in the most scientific way possible. From 1960 on, a series of more forceful schools of thought related to social and human sciences arose, with a decisive impact on the methodological basis of educational research. This paper presents and summarises some of the characteristics of research in education according to paradigms that lead us to confirm a variety of theoretical perspectives, providing a comprehensive, diverse and complementary framework of research method references for the construction of knowledge in the social and human sciences.